Organic composite photocatalysts from g-C3N4 and a soluble dibenzothiophene-S, S′-dioxide-containing polymer for hydrogen evolution. (17th October 2022) - Mao, Na; Jiang, Jia-Xing
Abstract : The inbuilt electric field of PHJ is advantageous for enhancing the photocatalytic activity of g-C3 N4 /PFSO composites. Abstract : The possibility of enhancing the hydrogen evolution performance of g-C3 N4 through constructing a heterojunction between g-C3 N4 and metal oxides or sulfides has been exploited recently. Herein, we report the design of organic composite heterojunctions of g-C3 N4 and a soluble dibenzothiophene- S, S -dioxide-containing polymer (PFSO). Constructing bulky heterojunctions by loading the soluble dibenzothiophene- S, S -dioxide-containing polymer on the surface of carbon nitride (g-C3 N4 ) nanosheets plays a significant role in enhancing their photocatalytic activity. Benefiting from the enhanced separation of photogenerated electrons and holes as well as a broadened light-absorption range of the heterojunction design, the composite of g-C3 N4 /PFSO-1 containing 1 wt% PFSO shows a high hydrogen evolution rate of 149 μmol h −1, which is 30 times higher than that of bare g-C3 N4 . This study provides insight into fabricating high-performance polymer-heterojunction photocatalysts for H2 production.